2017
DOI: 10.1002/jobm.201700467
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of acetyl CoA and lipid synthesis by PII protein in Synechococcus PCC 7942

Abstract: P protein family is widespread in prokaryotes and plants. In this study, impacts of P deficiency on the synthesis of acetyl CoA and acetyl CoA carboxylase enzyme (ACCase) was analyzed in the Synechococcus sp. PCC 7942 by evaluating the mRNA levels of pyruvate kinase (PK), pyruvate dehydrogenase (PDH), citrate synthase (CS), biotin synthase (BS), biotin carboxylase (BC), biotin carboxyl carrier protein (BCCP), carboxyl transferase (CT) α and β subunits. The P deficient Synechococcus sp. PCC 7942 showed upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The information related to FA synthesis regulation in Se7942 focuses on the signal transduction protein P II . The P II mutant strain of Se7942 showed a decreased intracellular acetyl-CoA content and enhanced activity of the acetyl-CoA–carboxylase complex through transcriptional activation of the accABCD genes [60]. However, P II does not regulate the enzymes involved in the FAS system.…”
Section: Discussionmentioning
confidence: 99%
“…The information related to FA synthesis regulation in Se7942 focuses on the signal transduction protein P II . The P II mutant strain of Se7942 showed a decreased intracellular acetyl-CoA content and enhanced activity of the acetyl-CoA–carboxylase complex through transcriptional activation of the accABCD genes [60]. However, P II does not regulate the enzymes involved in the FAS system.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the global regulator LexA was found to repress the expression of some fab genes (Kizawa et al, 2017), while a transcriptional regulator, CyAbrB2, was found to inhibit the FFA production in Syn6803 (Kawahara et al, 2016). The global nitrogen regulator PII protein was shown to negatively regulate cyanobacterial fatty acid biosynthesis by transcriptional control (Verma et al, 2018) or by interacting with biotin carboxyl carrier protein (BCCP) which is a subunit of ACCase (Hauf et al, 2016).…”
Section: Regulation Of Fatty Acid and Lipid Metabolisms In Cyanobacteriamentioning
confidence: 99%